A pessoa idosa no município de Cariacica: cidadania, legislação e mobilidade - Rafael, Lindomar Gonçalves (2014)
This paper aims at granting knowledge about the level of organization and the autonomy of the elderly person and raise awareness of the elderly person and of society, through diverse movements, to construct citizenship and carry out and apply the public policies of social nature. The work is composed of three basic and essential chapters. In the first chapter it highlights a reflection about Citizenship, Social Organization, Autonomy and Participation seen as challenges for the aging. It seeks to recover conceptual and historical aspects of Citizenship, Social Policies such as social assistance, in the process of the construction of Citizenship. In the second chapter it seeks to highlight the importance of getting to know the legislation in order to apply it to contribute to the well being of the population made up of elderly people. Highlighted throughout the chapter are the facts and stories which have taken place during the process of debates, elaboration and normatization of the current laws, besides the presentation of the main advances in urban mobility policies and the placement of the public space as an integral part of the so called social function in the life of the elderly person in their natural process of constantly coming and going. The third chapter presents the history of the Municipality of Cariacica, with its own characteristics. It gives a presentation of the social data and indicators of the municipality; the virtues and challenges of its urban development, highlighting the territorial organization plan and culminating with the presentation of projects such as: The Live Sidewalk and the Shoreline of Cariacica.